Alpheus leptochiroides De Man, 1909, a poorly known deep-water snapping shrimp with a unique third maxilliped (Malacostraca: Decapoda: Alpheidae) - Anker, Arthur; Fransen, Charles H.j.m. (Zootaxa, 2019)
Alpheus leptochiroides De Man, 1909, a poorly-known species originally described from the Kai Islands in eastern Indonesia, is reported from Kavieng, eastern Papua New Guinea, representing only the second record of this snapping shrimp and slightly extending its distribution range into the tropical western Pacific. The original description was based on a relatively young specimen, whereas the Kavieng specimen is clearly an adult male. Most importantly, several rather important characters of the species were omitted and/or not illustrated by De Man, including the unique and diagnostic rounded cuticular expansions on several areas of the third maxilliped, not present in any other alpheid shrimp. Therefore, a full redescription of the species is provided, with new detailed illustrations.